2014
DOI: 10.1155/2014/704395
|View full text |Cite
|
Sign up to set email alerts
|

Isolated IgA Anti-β2 Glycoprotein I Antibodies in Patients with Clinical Criteria for Antiphospholipid Syndrome

Abstract: Seronegative antiphospholipid syndrome (SNAPS) is an autoimmune disease present in patients with clinical manifestations highly suggestive of Antiphospholipid Syndrome (APS) but with persistently negative consensus antiphospholipid antibodies (a-PL). IgA anti-β2 Glycoprotein I (aB2-GPI) antibodies are associated with APS. However, they are not currently considered to be laboratory criteria due to the heterogeneity of published works and the use of poor standardized diagnostic systems. We have aimed to assess a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 36 publications
5
48
4
Order By: Relevance
“…Anti-b2GPI IgA might even provide a marker of seronegative APS, since this test has been shown to identify patients with manifestations highly suggestive of APS, but no consensus aPLs [40][41][42].…”
Section: Resultsmentioning
confidence: 99%
“…Anti-b2GPI IgA might even provide a marker of seronegative APS, since this test has been shown to identify patients with manifestations highly suggestive of APS, but no consensus aPLs [40][41][42].…”
Section: Resultsmentioning
confidence: 99%
“…In a large multi-center, multi-ethnic cohort (LUMINA), Murthy et al reported that isolated IgA anti-β2GPI was associated with thrombosis [125]. Ruiz-García et al reported that IgA anti-β2GPI was associated with primary APS [126], and similar findings were reported by Mattia et al [127]. None of these studies reported whether there was an association between smoking and the IgA antibodies in their patient population.…”
Section: Iga Autoantibodies and Smokingmentioning
confidence: 87%
“…The manufacturer's cutoff was perfectly comparable with that observed in the Spanish population. 19 Crossmatching between recipient (serum) and donor (lymphocyte suspension) was performed by cytolysis mediated by a specific antibody in the presence of complement. 56 Patients were transplanted only if the crossmatch was negative.…”
Section: Laboratory Determinationsmentioning
confidence: 99%
“…Only 14% of patients with C-APS were positive for any consensus antibody, whereas the presence of isolated IgA aB2GPI antibodies was found in 22% of patients with C-APS. 19 Although most of the works highlighted the value of IgA aB2GPI antibodies in the diagnosis of APS, the meaning of the presence of aB2GPI IgA antibodies is still under debate in the literature, because the available diagnostic tools have not been sufficiently standardized and the diagnostic assays used in some works with negative results were not optimal. 20 aPL antibodies of isotypes IgG and IgM are more frequent in patients with CKD than the general population.…”
mentioning
confidence: 99%